Phytochemical screening and the analysis of antibacterial activity in Chrysanthemum morifolium Ramat - Nowrid, Nazia (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.